On the study of a sample of Gasteropods (Prosobranchia) from the intertidal range of Azores - Arruda, Luís M. (1984)
According to MOTOMURA (1932), the geometrical progression law gives a good idea of the relative abundance of the animal species living in the intertidal region. The author's stay of the population structure of 23 mollusc, 5 echinoderm and 1 crustacean species from the different levels of the intertidal region lead to these conclusion (cf. INAGAKI, 1967). Nevertheless, MOTOMURA's deduction can be argued in two ways: on one hand, the tidal zone presents several environments at different levels and in distinct regions, and for this reason the structure of a settlement living in a homogeneous diverse environment is described by MACARTHUR's broken-stick model. On the other hand, the application of MOTOMURA's model demands the correct delimitation of the settlements which are submitted to the same environmental aspects. These give them the own individuality that can be seen in a specific characteristic profile which if it is not found, leads to the un-adjustment of the model. For these reasons, ARRUDA (1979 a, b; in press) in previous works dealing with intertidal fish studied the application of MOTOMURA's model to settlements living in different biotopes and compared the goodness of the adjustments obtained. This present work aims to test the model's adjustment to a gastropod community intertidal prosobranchs living under accentuated hydrodynamic conditions and subjected to intensive fishing at Laginha, a place around an island (Fayal) of the Azores archipelago. The coast of these islands is difficult to approach, being formed by huge irregular rock formations or by vertical cliffs to the sea. So a pahoehoe type lava area with a slight declivity was chosen as fieldwork. There it is possible to approach the surf me during low tide. It must be referred to as a point d interest, that limpets are much consumed on these islands and so their commercial value should not be under-estimated. Those environmental conditions make the collecting of these species easier.